The relatives came - Rylant, Cynthia; Gammell, Stephen (New York : Aladdin Paperbacks, 1993)
The relatives come to visit from Virginia and everyone has a wonderful time.
Caldecott Medal/Honor.
Elem. School Library Collection.
Wilson's Children.
Book Links (A.L.A.), May 2000.
Booklist, July 2006.
Bulletin (Center for Children's books), April 2007.
Keywords: Family life -- Fiction; Family life -- Fiction